Pescando con Pedro = Fishing with Peter - Harvey, Diane Kelsay, 1946-; Harvey, Bob, 1952- (Wilsonville, Or. : Beautiful America Pub. Co., 1993)
Text in English and Spanish discusses the way of life of brown pelicans and other fishing birds in the unique salt water environment along the coast of Belize, a habitat which is now threatened.
Text in English and Spanish.
"A Little America book."
Keywords: Water birds -- Belize -- Juvenile literature; Sea birds -- Belize -- Juvenile literature; Brown pelican; Pelicans; Water birds -- Belize; Birds -- Belize; Wildlife conservation -- Belize; Spanish language materials -- Bilingual